Effect of Instructional Guides (Ig) on The Academic Performance of Grade 9 TLE Food Technology Students - Banguis, Chinibeth F.; Calipayan, Jr., Jose P. (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aimed to determine the effect of instructional guides on the academic achievement of Grade 9 students in Food Technology. Specifically, it compared students’ mean scores when taught with and without instructional guides and examined the significance of differences in achievement when grouped by Technical Competence Level. A quasi-experimental design was utilized, where one group received instruction using a structured guide, while another received traditional methods. Findings showed that students taught with instructional guides performed significantly better than those without, particularly among students with varying levels of technical competence. The study concluded that instructional guides are effective in enhancing students’ learning outcomes in Food Technology, as they provide structured, accessible content that supports varied learning abilities. Recommendations include implementing instructional guides broadly for technical subjects, encouraging teachers to incorporate similar structured tools, and further research into other subjects to assess potential benefits of instructional guides in different educational contexts.